The Association Between Nonsteroidal Anti-Inflammatory Drug Use and Inflammatory Bowel Disease Exacerbations: A True Association or Residual Bias?. (12th November 2022) - Cohen-Mekelburg, Shirley; Van, Tony; Wallace, Beth; Berinstein, Jeff; Yu, Xianshi; Lewis, James; Hou, Jason; Dominitz, Jason A.; Waljee, Akbar K.
Abstract : INTRODUCTION: Studies suggest that nonsteroidal anti-inflammatory drugs (NSAID) may contribute to inflammatory bowel disease (IBD) exacerbations. We examined whether variation in the likelihood of IBD exacerbations is attributable to NSAID. METHODS: In a cohort of patients with IBD (2004–2015), we used 3 analytic methods to examine the likelihood of an exacerbation after an NSAID exposure. First, we matched patients by propensity for NSAID use and examined the association between NSAID exposure and IBD exacerbation using an adjusted Cox proportional hazards model. To assess for residual confounding, we estimated a previous event rate ratio and used a self-controlled case series analysis to further explore the relationship between NSAID and IBD exacerbations. RESULTS: We identified 15, 705 (44.8%) and 19, 326 (55.2%) IBD patients with and without an NSAID exposure, respectively. Findings from the Cox proportional hazards model suggested an association between NSAID and IBD exacerbation (hazard ratio 1.24; 95% confidence interval 1.16–1.33). However, the likelihood of an IBD exacerbation in the NSAID-exposed arm preceding NSAID exposure was similar (hazard ratio 1.30; 95% confidence interval 1.21–1.39). A self-controlled case series analysis of 3, 968 patients who had both an NSAID exposure and IBD exacerbation demonstrated similar exacerbation rates in the 1 year preceding exposure, 2–6 weeks postexposure, and 6 weeks to 6 months postexposure, but a higher incidence in 0–2 weeks postexposure, suggesting potential confounding by reverse causality. DISCUSSION: While we see an association between NSAID and IBD exacerbations using traditional methods, further analysis suggests this may be secondary to residual bias. These findings may reassure patients and clinicians considering NSAID as a nonopioid pain management option. Abstract :